2016
DOI: 10.1038/ncomms10952
|View full text |Cite
|
Sign up to set email alerts
|

Understanding silicate hydration from quantitative analyses of hydrating tricalcium silicates

Abstract: Silicate hydration is prevalent in natural and technological processes, such as, mineral weathering, glass alteration, zeolite syntheses and cement hydration. Tricalcium silicate (Ca3SiO5), the main constituent of Portland cement, is amongst the most reactive silicates in water. Despite its widespread industrial use, the reaction of Ca3SiO5 with water to form calcium-silicate-hydrates (C-S-H) still hosts many open questions. Here, we show that solid-state nuclear magnetic resonance measurements of 29Si-enriche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 53 publications
10
106
0
Order By: Relevance
“…41,48,[81][82][83][84][85][86] However, it is also necessary to study the interaction between the different phases that might induce other reactions or kinetics as in pure phases systems. Lerch 87 and later Tenoutasse 30 illustrated in particular the importance of the balance between the silicates, the aluminates and the sulfates ( Figure SB3.2).…”
Section: Silicate-aluminate-sulfate Balancementioning
confidence: 99%
“…41,48,[81][82][83][84][85][86] However, it is also necessary to study the interaction between the different phases that might induce other reactions or kinetics as in pure phases systems. Lerch 87 and later Tenoutasse 30 illustrated in particular the importance of the balance between the silicates, the aluminates and the sulfates ( Figure SB3.2).…”
Section: Silicate-aluminate-sulfate Balancementioning
confidence: 99%
“…The literature includes descriptions of slightly different hydration reactions for alite, which lead to calcium silicate hydrate gels with slightly different densities and compositions [5][6][7][8]. Here, we have chosen the Ca-to-Si average ratio of 1.8, because it is compatible with many previous reports, which gave values ranging from 1.7-2.0.…”
Section: Cementsmentioning
confidence: 99%
“…Advances in geochemistry helped support the notion that typical pore solutions are indeed close to the apparent experimental solubility of alite, explaining why its dissolution rate drastically decreases few seconds/minutes after the first contact with water. In parallel, it was observed that protonation of silicate monomers and free oxygen atoms strongly stabilize alite surface and reduce its solubility [30,50]. As mentioned earlier, the surface bonding of ions [33,51] or the adsorption of polymers [42] also stabilize the alite surface and in turn extend the dormant period.…”
Section: Dormant Periodmentioning
confidence: 72%